2019
DOI: 10.1093/molehr/gaz034
|View full text |Cite
|
Sign up to set email alerts
|

Continuous behavioural ‘switching’ in human spermatozoa and its regulation by Ca2+-mobilising stimuli

Abstract: Human sperm show a variety of different behaviours (types of motility) that have different functional roles. Previous reports suggest that sperm may reversibly switch between these behaviours. We have recorded and analysed the behaviour of individual human sperm (180 cells in total), each cell monitored continuously for 3–3.5 min either under control conditions or in the presence of Ca2+-mobilising stimuli. Switching between different behaviours was assessed visually (1 s bins using four behaviour categories),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
(47 reference statements)
1
6
0
Order By: Relevance
“…However, this change is not immediate, it occurs after a significant time-delay (~75 s). In contrast, the control sperm depicted in red remains stable and only shows a large increase in beating frequency towards the end of the imaging period, demonstrating the potential for spontaneous self-switching, in agreement with earlier observations (Achikanu et al, 2019). Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, this change is not immediate, it occurs after a significant time-delay (~75 s). In contrast, the control sperm depicted in red remains stable and only shows a large increase in beating frequency towards the end of the imaging period, demonstrating the potential for spontaneous self-switching, in agreement with earlier observations (Achikanu et al, 2019). Fig.…”
Section: Resultssupporting
confidence: 91%
“…This latter mode of flagellar beating is named hyperactivation and is necessary for fertilization (Chang & Suarez, 2011). Its characteristics can vary among species and even within the same cell population (Drobnis et al, 1988;Ravaux et al, 2016), indicating possible functional switching between different sperm behaviors (Achikanu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, though we might report the frequency of the flagellar beat as a single value, the actual frequency may be evolving with time. Of particular note, the recent study of Achikanu et al (2019) tracked sperm motion over a considerable time period, identifying sustained behavioural switching that is more significant than we have hinted at here, highlighting the significance of careful temporal considerations of the spermatozoan beat and its descriptors.…”
Section: Summary Statisticsmentioning
confidence: 57%
“…One study showed that sperm from NEP2 knockout mice had normal characteristics but lower fertilization capacity, and resulting embryos had a worse development [91]. Inhibition of NEP and NEP2 by phosphoramidon leads to an increase in linear and straight motility of sperm cells (sperm progressive motility), which is essential for adequate swimming through the female genital tract [92][93][94].…”
Section: Spermatozoa Functionmentioning
confidence: 99%